The Diversity of PAH-degrading bacteria in a deep-sea water column above the Southwest Indian Ridge - Shao, Zongze; Yuan, Jun; Lai, Qiliang; Zheng, Tianling (Frontiers in Microbiology, 2015)
The bacteria involved in organic pollutant degradation in pelagic deep-sea environments are largely unknown. In this report, the diversity of polycyclic aromatic hydrocarbon ( PAH)-degrading bacteria was analyzed in deep-sea water on the Southwest Indian Ridge (SWIR). After enrichment with a PAH mixture (phenanthrene, anthracene, fluoranthene and pyrene), 9 nine bacterial consortia were obtained from depths of 3946 m to 4746 m. PAH degradation occurred to all components of the mixture, but when using a single PAH as the sole carbon and energy source, only phenanthrene can be degraded obviously. This indicates the cometabolism of anthracene, fluoranthene and pyrene with phenanthreneWhile the consortia degraded all four PAHs when supplied in a mixture, when PAHs were tested individually, only phenanthrene supported growth. Thus, degradation of the PAH mixture reflected a cometabolism of anthracene, fluoranthene and pyrene with phenanthrene. Further, both culture-dependent and independent methods revealed many new bacteria involved in PAH degradation. Specifically, the alpha and gamma subclasses of Proteobacteria were confirmed as the major groups within the communities. Additionally, Actinobacteria, the CFB group and Firmicutes were detected. Denaturing Gradient Gel Electrophoresis (DGGE) analysis showed that bacteria closely affiliated with Alcanivorax, Novosphingobium and Rhodovulum occurred most frequently in different PAH-degrading consortia. More than half of the isolates (34 of 51 isolates) were confirmed to have the ability to grow with the PAH mixture By using general heterotrophic media, 51 bacteria were isolated from the consortia and of these 34 grew with the PAH mixture as a sole carbon source. Of these, isolates most closely related to Alterierythrobacter, Citricella, Erythrobacter, Idiomarina, Lutibacterium, Maricaulis, Marinobacter, Martelella, Pseudidiomarina, Rhodobacter, Roseovarius, Salipiger, Sphingopyxis and Stappia were found to be PAH degraders.